Innovation infrastructure and innovation climate: innovation development ecosystem - K. Yu. Kulakov; N. G. Verstina; T. S. Meshcheryakova (E-Management, 2022)
The fourth industrial revolution “Industry 4.0” defines a paradigm shift in technological patterns, requiring the modernization of the institutional environment in the context of the development of end-to-end technologies. This fact determines the need for analysis and subsequent development of innovation infrastructure subsystems. The system-forming elements of the innovative development of the national and regional economies are: scientific activities of educational, research, expert organizations; venture forms of entrepreneurship; innovative enterprises and clusters; regulatory and legislative regulators; attributive mechanisms of innovative development and subjects of the innovative environment. The progressive development of the elements and subsystems of the innovation infrastructure determines the need for a systematic representation of the innovation environment. The aim of the study is to analyze the innovation infrastructure and ecosystem in the Russian Federation. The article discusses the categories of “innovation infrastructure” and “innovation ecosystem”, which are becoming increasingly widespread in the scientific literature and government documents, while being used in similar semantic contexts. The key objectives of the study, described in the theoretical part of the work, are the analysis of the elements of the innovation infrastructure and the innovation climate of the territories of federal districts and regions. The study uses general scientific research methods. The information base of the study is the data of federal authorities, research and analytical centers, international consulting companies, publications of Russian and foreign experts. The results obtained are of an applied nature, since they reflect the problem areas and directions for the development of the innovation ecosystem. The main problem is the lack of a single effective approach to managing innovation processes in the Russian Federation, despite the multiplicity of infrastructure elements in the national and regional innovation systems. This aspect is debatable, but the discreteness of the process of developing the national innovation infrastructure is obvious, which does not allow for the functioning of a self-developing open innovation ecosystem.